Oligomannose-Rich Membranes of Dying Intestinal Epithelial Cells Promote Host Colonization by Adherent-Invasive E. coli - Dumych, Tetiana; Yamakawa, Nao; Sivignon, Adeline; Garenaux, Estelle; Robakiewicz, Stefania; Coddeville, Bernadette; Bongiovanni, Antonino; Bray, Fabrice; Barnich, Nicolas; Szunerits, Sabine; Slomianny, Christian; Herrmann, Martin; et al. (Frontiers in Microbiology, 2018)
A novel mechanism is revealed by which clinical isolates of adherent-invasive Escherichia coli (AIEC) penetrate into the epithelial cell layer, replicate, and establish biofilms in Crohn's disease. AIEC uses the FimH fimbrial adhesin to bind to oligomannose glycans on the surface of host cells. Oligomannose glycans exposed on early apoptotic cells are the preferred binding targets of AIEC, so apoptotic cells serve as potential entry points for bacteria into the epithelial cell layer. Thereafter, the bacteria propagate laterally in the epithelial intercellular spaces. We demonstrate oligomannosylation at two distinct sites of a glycoprotein receptor for AIEC, carcinoembryonic antigen related cell adhesion molecule 6 (CEACAM6 or CD66c), on human intestinal epithelia. After bacterial binding, FimH interacts with CEACAM6, which then clusters. The presence of the highest-affinity epitope for FimH, oligomannose-5, on CEACAM6 is demonstrated using LC-MS/MS. As mannose-dependent infections are abundant, this mechanism might also be used by other adherent-invasive pathogens.